KOLABORASI LEADING SECTOR DENGAN MITRA BKKBN DAN DINKES SELUMA DALAM PENDAMPINGAN DAPUR DAHSAT KELUARGA BALITA STUNTING DI KABUPATEN SELUMA - Kamsiah, Kamsiah; Yuliantini, Emy; Pravita Sari, Ayu; Eliana, Eliana; Widiyanti, Desi; Maryati, Maryati (Poltekkes Kemenkes Bengkulu, 2023)
Stunting is caused by low nutritional intake over a long period of time and/or frequently suffering from infectious diseases. The approach that can be taken is community empowerment. Efforts to implement DAHSAT to prevent stunting are carried out by increasing the knowledge of mothers of toddlers regarding toddler food intake by assisting the implementation of the DAHSAT kitchen for toddler families in Seluma Regency. The targets of this community service activity are BKKBN Partners, mothers of babies/toddlers, the Seluma Health Office. The implementation method uses the lecture method with presentation techniques for accompanying material on the application of the DAHSAT kitchen, followed by demonstrations and discussions, Focus Group Discussions (FGD), Observations, while the problem of the ability to develop the knowledge of mothers of toddlers is resolved by providing training. This activity is packaged in the form of a workshop. There is an increase in the knowledge and skills of mothers of babies/toddlers in carrying out the practice of measuring weight and TB (anthropometry) in improving health and preventing stunting during toddler posyandu activities in Seluma Regency Village. BKKBN Seluma Regency, Poltekkes Kemenkes Bengkulu, Kungkai Baru Village and Puskesmas Air Periukkan continue to collaborate with partners to improve the management of Healthy Kitchens so that they are more active and move towards accelerating stunting reduction as evidence of the pentahelix collaboration at the Air Periukkan regional level, Seluma Regency.